2008
DOI: 10.1016/j.mimet.2008.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Skim milk enhances the preservation of thawed −80 °C bacterial stocks

Abstract: The results from bacterial strain recovery efforts following hurricanes Katrina and Rita are reported. Over 90% of strains frozen in 10% skim milk were recovered whereas various recovery rates were observed for glycerol-stored stocks (56% and 94% of E. coli, depending upon the laboratory). These observations led to a viability comparison of Streptococcus pyogenes, Campylobacter jejuni, Borrelia burgdorferi, Salmonella enterica subsp. Typhimurium, Pseudomonas aeruginosa and Escherichia coli strains stored in gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 27 publications
0
36
0
4
Order By: Relevance
“…Cultures may be stored for up to a week under microaerobic conditions at 4 C. For longer-term storage, cultures can be frozen in a cryopreservative, such as 10 % skim milk (Cody et al 2008) or 5 % glycerol, and stored at À80 C or in liquid nitrogen. Cultures can last for years but may require enrichment for recovery of damaged cells.…”
Section: Preservationmentioning
confidence: 99%
“…Cultures may be stored for up to a week under microaerobic conditions at 4 C. For longer-term storage, cultures can be frozen in a cryopreservative, such as 10 % skim milk (Cody et al 2008) or 5 % glycerol, and stored at À80 C or in liquid nitrogen. Cultures can last for years but may require enrichment for recovery of damaged cells.…”
Section: Preservationmentioning
confidence: 99%
“…P. aeruginosa can be preserved in frozen stocks of either 20% glycerol or 10% skim milk (Cody et al, 2008) that can be stored at −80°C. Growing bacteria on fresh plates from frozen stocks is important when starting experiments to ensure consistent results, particularly for clinical isolates from CF samples, as they can have very high mutation rates.…”
Section: Basic Protocol 1: Growth Of P Aeruginosa From a Frozen Stockmentioning
confidence: 99%
“…It has been reported that viability of frozen stocks may be improved when they are prepared in 10% skim milk instead of glycerol ( Cody et al, 2008). …”
Section: Basic Protocol 3: Preparation Of P Aeruginosa Frozen Stocksmentioning
confidence: 99%
“…Under some circumstances refrigeration and freezing could be impracticable (Cody et al 2008). Hence, to maintain microbial cultures at room temperature is paramount.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains and culture preparation: Strains C26 and C27 were isolated from eucalyptus rhizosphere in Codazzi, Cesar, Colombia (Obando (Cody et al 2008, and routine method in our Lab) since these show to be highly effective to preserve viability of many Gramnegative bacteria. Finally, for immobilization in dried polymers we used alginate (Bashan and Gonzales 1999), acacia gum (Krumnow et al 2009), carrageenan (Denkova et al 2004), and Polyox ® that was first evaluated in this study.…”
Section: Methodsmentioning
confidence: 99%